ADMINISTRATION AND REALIZATION OF SCHOOL, COLLEGE, AND NON-FORMAL EDUCATION ACCREDITATION CERTIFICATION - Kms.Badaruddin; Depi Kurniati; Yanuar Arafat; Zailia (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Accreditation is carried out as an effort to improve quality in the field of education, the aim is to improve quality which covers all aspects of education in the form of science, administration teaching, and educational staff. Accreditation activities contain a comprehensive assessment process of the suitability of an educational unit or program, as a form of recognition for the provision of education in an educational unit. In this discussion, we will discuss and explain educational accreditation. By using the literature review or literature study method. The results of this discussion explain that accreditation is defined as a process of evaluating and assessing the quality of an institution or institutions carried out by a team of experts who we as assessors are based on predetermined quality standards. To further encourage Pre-Schools, Schools or Islamic Schools, Non-Formal Education, and Higher Education institutions to always strive to improve quality in various aspects and in order to increase accountability to the wider community, efforts to provide accreditation for educational institutions at every level are a very important need. Accreditation will achieve maximum results if each PAUD, School/Madrasah, Non-Formal Education, and Higher Education Institution always carries out regular and ongoing self-evaluations in an objective, honest, and transparent manner.